Pre-Post tentang Pengetahuan Ibu Mengenai Deteksi Dini Kanker Serviks setelah Pendidikan Kesehatan dengan Media Leaflet di Yayasan Harapan Anak Indonesia Jakarta Utara Tahun 2025 - Diana Putri Febriana; Ade Heryana; Namira Wadjir Sangadji; Dwi Nurmawaty (Pusat riset dan Inovasi Nasional, 2025)
Cervical cancer remains one of the leading causes of death among women, particularly in developing countries such as Indonesia. This disease is largely preventable through early detection efforts; however, low levels of knowledge and awareness among women of reproductive age often hinder them from undergoing routine screening. Limited information leads to most new cases being diagnosed at advanced stages, thereby lowering treatment success rates and increasing the public health burden. This study aimed to analyze the differences in knowledge among mothers at Yayasan Harapan Anak Indonesia, North Jakarta, regarding early detection of cervical cancer before and after receiving health education using leaflets. The study employed a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 40 reproductive-age women selected using total sampling. A structured questionnaire was used as the research instrument, covering questions about the definition, risk factors, symptoms, and early detection methods of cervical cancer. The intervention was carried out through a lecture accompanied by leaflet distribution, which provided concise, clear, attractive, and easy-to-understand information. Data were analyzed using paired t-tests to evaluate differences in mean scores before and after the intervention. The results showed an increase in the mean knowledge score from 57.69 in the pretest to 88.08 in the posttest. Statistical analysis revealed a significant difference (p<0.05) between pre- and post-intervention. The study concludes that health education using leaflets is effective in improving mothers’ knowledge about cervical cancer early detection. Health workers are recommended to expand educational coverage using simple printed media as a sustainable strategy for prevention, to enhance community awareness more broadly, and ultimately to reduce cervical cancer incidence.